PENINGKATAN KESADARAN IMUNISASI PADA ANAK-ANAK DI KOTA MEDAN: EVALUASI DAMPAK PROGRAM PENDIDIKAN MASYARAKAT - PAUL SAUT MARGANDA LUMBAN TOBING (LP2MTBM MAKARIOZ, 2022)
The immunization program in Medan City is less enthusiastic, so thousands of other children have not immunized massively, where the problem is the lack of effective vaccination, where this can be seen from the number of children who are sick in Medan City of 12,105 people, where this number is very large, so massive socialization is needed to parents about the importance of vaccination for children. In addition to the effectiveness of vaccination, low awareness from parents has also triggered this program has not targeted all children in Medan City with 586,082 people or around (2.06%) of the number of children in Medan City. This study used descriptive analytical method. The population of this study amounted to 12,105 parents whose children had not been immunized through the immunization program from the Government in 2022, where the sample taken amounted to 65 parents whose children had not been immunized through the immunization program from the Government in 2022. The results of the study proved that the number of children who participated in immunization were children aged in the range of 0-4 years, as well as many children who had not participated in immunization in Medan Kota District which resulted in the existing vaccination program being ineffective due to lack of awareness in carrying out immunization programs, as well as lack of socialization from the Government and Health Office about the importance of immunization, and no impact on the immunization process on education and community literacy About immunization and prevention of the spread of disease.